Fit & well core concepts and labs in physical fitness and wellness - Fahey, Thomas D. (Thomas Davin) 1947-; Insel, Claire; Insel, Paul M.; Roth, Walton T. (McGraw-Hill Education, 2023)
McGraw-Hill Connect is a digital teaching and learning environment that improves performance over a variety of critical outcomes; it is easy to use, and it is proven effective. Connect empowers students to achieve better outcomes by continually adapting to deliver precisely what they need, when they need it, and how they need it, so your class time is more engaging and effective. Connect for Fit & Well offers a wealth of interactive online content, including fitness and wellness labs and self-assessments, video activities on timely health topics and exercise techniques, a behavior change workbook, and practice quizzes with immediate feedback. The Connect eBook makes it easy for students to access their reading materials on smartphones and tablets; they can study on the go and don't need internet access to use it